Broad Diversity of Fungi in Hospital Water - Máira Gazzola Arroyo; Adriano Menis Ferreira; Oleci Pereira Frota; Natalia Seron Brizzotti-Mazuchi; Jacqueline Tanury Macruz Peresi; Marcelo Alessandro Rigotti; Carlos Eduardo Macedo; Alvaro Francisco Lopes de Sousa; Denise de Andrade; Margarete Teresa Gottardo de Almeida (The Scientific World Journal)
Introduction. Some studies have reported the occurrence of microorganisms isolated from water. Considering these microorganisms, fungi are known to occur ubiquitously in the environment, including water, and some are pathogenic and may cause health problems, especially in immunocompromised individuals. The aim of this study was to identify fungi in hospital water samples and to correlate their presence with the concentration of free residual chlorine. Methods. Water samples (100 mL) were collected from taps (n = 74) and water purifiers (n = 14) in different locations in a university hospital. Samples were filtered through a nitrocellulose membrane and placed on Sabouraud dextrose agar and incubated for 24 hours at 30∘C. Fungi were identified according to established methods based on macroscopic and microscopic characteristics (filamentous) and physiological tests (yeasts). Free chlorine residual content was measured at the time of sample collection. Results. Seventy species of fungi were identified in the water samples and about 56% of the water samples contained culturable fungi. Cladosporium oxysporum, Penicillium spinulosum, and Aspergillus fumigatus were the most common filamentous fungi. Aureobasidium pullulans and Candida parapsilosis were the most common yeasts. Chemical analyses revealed that free residual chlorine was present in 81.8% of the samples within recommended concentrations. Among samples from water purifiers, 92.9% showed low levels of free residual chlorine (<0.2 mg/L). There was no significant association between chlorine concentrations (either within or outside the recommended range) and the presence of filamentous fungi and yeasts. Conclusions. This study showed that hospital water can be a reservoir for fungi, some of which are potentially harmful to immunocompromised patients. Free residual chlorine was ineffective in some samples.